Anatomy of motor learning. I. Frontal cortex and attention to action. - Jueptner, M; Stephan, K; Frith, C; Brooks, D; Frackowiak, R; Passingham, R (1997)
We used positron emission tomography to study new learning and automatic performance in normal volunteers. Subjects learned sequences of eight finger movements by trial and error. In a previous experiment we showed that the prefrontal cortex was activated during new learning but not during during automatic performance. The aim of the present experiment was to see what areas could be reactivated if the subjects performed the prelearned sequence but were required to pay attention to what they were doing. Scans were carried out under four conditions. In the first the subjects performed a prelearned sequence of eight key presses; this sequence was learned before scanning and was practiced until it had become overlearned, so that the subjects were able to perform it automatically. In the second condition the subjects learned a new sequence during scanning. In a third condition the subjects performed the prelearned sequence, but they were required to attend to what they were doing; they were instructed to think about the next movement. The fourth condition was a baseline condition. As in the earlier study, the dorsal prefrontal cortex and anterior cingulate area 32 were activated during new learning, but not during automatic performance. The left dorsal prefrontal cortex and the right anterior cingulate cortex were reactivated when subjects paid attention to the performance of the prelearned sequence compared with automatic performance of the same task. It is suggested that the critical feature was that the subjects were required to attend to the preparation of their responses. However, the dorsal prefrontal cortex and the anterior cingulate cortex were activated more when the subjects learned a new sequence than they were when subjects simply paid attention to a prelearned sequence. New learning differs from the attention condition in that the subjects generated moves, monitored the outcomes, and remembered the responses that had been successful. All these are nonroutine operations to which the subjects must attend. Further analysis is needed to specify which are the nonroutine operations that require the involvement of the dorsal prefrontal and anterior cingulate cortex.